Assessment of solid waste separation practices : a case study of the AIT campus - Khalil, Marzia; Ekbordin Winijkul; Thammarat Koottatep; Ahmad, Mokbul Morshed; Ministry of HigherEducation (MoHE), Afghanistan; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Solid Waste Management is one of the most significant problems for achieving sustainability in any places. The goal of this study was to assess the existing solid waste separation practicesin AIT campus, by estimatingthe solid waste generation rate, physical characterization and composition of solid wastesin academic, residential, and commercial areain AIT. The waste generation rates were0.9, 0.2 and 0.4tonsper dayin residential, academic and commercial area in AIT, respectively. The estimated per capita solid waste generation rate was0.5 kg/capita/day. It is expected, however, that the solid waste characteristics for the AIT campus wouldchange over time. The institution generated544 tons/yearof solid waste, which wasnearly 0.5 kg/day/person. Food wastesand plastic wastes hadthe highest compositionof28%, followed by plastic waste of 28%. The wasteshad moisture contentof 47 %, and bulk density was120 kg/m3.Waste separation wasnot successfulin AIT, and the mixed wasteswerefoundin different color garbage bins, temporarily storedat the material recovery facility,and finally sentto local Thai Municipality for final disposal. People mixed all the waste in the dormitory (usually only one bin was provided in each room in the resident area) and droppedto the bins. The plastic wastegeneration rate was481.6 kg/daywhich was collected from three color bins.This study, however, showedthat there wasa potentialfor better separation ofsolid wastes.The physical analysis of the solid wastesshowed that 28% of the total solid wastesgenerated was plastics, which showed the lack of awareness of using plastic products inAIT. In this study, the recommendation was to change from three colored garbage bin system to two garbage bin systems (only wet and day) with proper pictures of wastes posted in front of eachbin. Also, number of required garbage bins by colors were provided as a recommendation for better management of garbage bin locations on AIT campus.The application of solid waste management and waste separation conducted inAIT campus could be apply to Kabul city, Afghanistan. The questionnaire survey and waste generation and composition analysis could be used to assess the current solid waste situation and provide recommendation for better solid waste management in Kabul city.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M. Sc.) - Asian Institute of Technology, 2018
Keywords: Refuse and refuse disposal -- Thailand (AIT campus) -- Management; Refuse and refuse disposal -- Developing countries -- Management